2013
DOI: 10.1111/mmi.12352
|View full text |Cite
|
Sign up to set email alerts
|

The cooperative roles of PHO80‐like cyclins in regulating the G1/S transition and posterior cytoskeletal morphogenesis in Trypanosoma brucei

Abstract: Cyclins and cyclin-dependent kinases (CDKs) represent the fundamental, crucial regulators of the cell division cycle in eukaryotes. Trypanosoma brucei expresses a large number of cyclins and Cdc2-related kinases (CRKs). However, how these cyclins and CRKs cooperate to regulate cell cycle progression remains poorly understood. Here, we carry out directional yeast two-hybrid assays to identify the interactions between the 10 cyclins and the 11 CRKs and detect a total of 26 cyclin-CRK pairs, among which 20 pairs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 30 publications
3
36
0
Order By: Relevance
“…Immunofluorescence microscopy showed that CRK1-PTP was detected in many punctate dots in the cytosol (Fig. 3C), as reported previously (27), and it co-localized with Sec31-HA at the ERES (Fig. 3C).…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Immunofluorescence microscopy showed that CRK1-PTP was detected in many punctate dots in the cytosol (Fig. 3C), as reported previously (27), and it co-localized with Sec31-HA at the ERES (Fig. 3C).…”
Section: Resultssupporting
confidence: 86%
“…5, A and B), suggesting that CRK1 is required for TbGRASP localization. CRK1 is known to associate with four PHO80-like cyclins, CYC2, CYC4, CYC5, and CYC7 (27). However, only the depletion of CYC2 or CYC7 generated cells with an elongated posterior, as the depletion of CRK1 (27), suggesting that CYC2 and CYC7 play specialized functions with CRK1.…”
Section: C H and I)mentioning
confidence: 99%
See 3 more Smart Citations